2012
DOI: 10.4318/tjg.2012.0423
|View full text |Cite
|
Sign up to set email alerts
|

The dual modulatory effect of folic acid supplementation on indomethacin- induced gastropathy in the rat

Abstract: Girifl ve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…It was reported that the oxidative stress in gastric tissue causes damage to key biomolecules such as lipids. In conjunction with the report of [64][65][66], the present study recorded elevations in the levels of the end products of lipid peroxidation, malondialdehyde (MDA) in the gastric tissues following SGU. The elevation in MDA suggests enhanced lipid peroxidation leading to tissue damage and failure of antioxidant defense mechanisms to prevent the formation of excessive free radicals.…”
Section: Discussionsupporting
confidence: 80%
“…It was reported that the oxidative stress in gastric tissue causes damage to key biomolecules such as lipids. In conjunction with the report of [64][65][66], the present study recorded elevations in the levels of the end products of lipid peroxidation, malondialdehyde (MDA) in the gastric tissues following SGU. The elevation in MDA suggests enhanced lipid peroxidation leading to tissue damage and failure of antioxidant defense mechanisms to prevent the formation of excessive free radicals.…”
Section: Discussionsupporting
confidence: 80%
“…and the ligation of the pylorus, induced histological lesions in mucosal and submucosal regions as revealed by histological examinations compared to control group (Figure 4). This finding conforms to that of several studies in which ulcer was induced using indomethacin [8,70,71] . …”
Section: Histopathological Studiessupporting
confidence: 92%
“…On the 15th-day of pretreatment or vehicle administration and after 36 hours of starvation, rats were anesthetized with ether inhalation, carefully dissected, and exposed to pyloric-ligation [43] for gastric juice collection. After that, indomethacin (25 mg/kg) [44,45] was injected intra-peritoneally, excluding the normal control group which received a single intra-peritoneal injection of 1% saline solution with Tween 80 (vehicle of indomethacin). After 4 h, rats were killed by cervical dislocation under ether anesthesia.…”
Section: Methodsmentioning
confidence: 99%